Reactivity of 2-and 4-Vinylpyrrole as Diene System towards dienophiles - M. Hania, Majed (Asian Journal of Chemistry, 2010)
IR and 1H-NMR spectral data of 2- and 4-vinylpyrrole derivatives (1) and (2), respectively, indicate that the reactivity of compound (1) is higher than that of (2) towaids–dienophiles. Analysis of [4π + 2] cycloaddition reaction of vinylpyrrole derivatives (1) and (2) with dimethylacetylene-dicarboxylate (DMAD) has been studied to reflect the higher reactivity of compound (2).